Shortened Duration of Dual Antiplatelet Therapy Following Percutaneous Coronary Intervention: A Contemporary Clinical Review - Kevin S Tang; Shoujit Banerjee; George Tang; Pranav M Patel; Antonio H Frangieh (Interventional Cardiology: Reviews, Research, Resources)
Percutaneous coronary intervention with stent implantation is an integral aspect of minimally interventional cardiac procedures. The technology and techniques behind stent design and implantation have evolved rapidly over several decades. However, continued discourse remains around optimal peri- and post-interventional management with dual antiplatelet therapy to minimise both major cardiovascular or cerebrovascular events and iatrogenic bleeding risk. Standard guidelines around dual antiplatelet therapy historically recommended long-term dual antiplatelet therapy for 12 months (with consideration for >12 months in certain patients); however, emerging data and generational improvements in the safety of drug-eluting stents have ushered in a new era of short-term therapy to reduce the incidence of major bleeding events. This case review will provide an overview of the current state of guidelines around duration of dual antiplatelet therapy and examine recent updates and continued gaps in existing research.